Effect of Young's modulus on fatigue crack growth. (March 2020) - Borges, M.F.; Antunes, F.V.; Prates, P.A.; Branco, R.; Vojtek, T.
Highlights: The effect of Young's modulus on FCG was predicted numerically using the plastic CTOD. The influence of E was found to be relevant comparatively to other material properties. A linear relation was found between 1/E and the plastic CTOD. The linearity exists independently of material, specimen geometry and stress state. Abstract: The objective here is to study the effect of Young modulus, E, on fatigue crack growth using a numerical approach which assumes that plastic CTOD is the crack driving force. The influence of E was found to be relevant comparatively to other material properties. A linear relation was found between 1/E and the plastic CTOD, and therefore the FCG rate, which is according most of the models proposed in literature. The decrease of rigidity increases the global elastic deformation of the component, and therefore crack tip plastic deformation. The linearity between plastic CTOD and 1/E was kept with crack closure.